EFEKTIVITAS LARUTAN DAN PARUTAN KUNYIT DALAM MENGAWETKAN IKAN BANDENG (CHANOS CHANOS) - Sri Ayu; Erlani Rappe (Politeknik Kesehatan Kemenkes Makassar, 2021)
ABSTRACT In the content contained in milkfish such as protein and fat is a suitable medium for the growth of spoilage bacteria or other microorganisms. One way to maintain its quality by providing preservatives to inhibit bacterial growth is to provide natural preservatives such as turmeric.The purpose of this study was to determine the effectiveness of turmeric as a preservative for milkfish (chanos chanos). This research is a quasi-experimental type of research, namely the treatment of the use of turmeric grater and solution as a preservative in milkfish (chanos chanos) to determine the physical durability of milkfish.The results of the physical condition examination were seen from the appearance of the eyes, surface mucus, meat, body texture in the preservation of milkfish using 65 grams of turmeric solution, showing contact time 1 hour, 8 hours, 16 hours, 21 hours organoleptic value did not exceed the minimum limit of 7, but contact time 22 hours shelf life has been damaged. The results of physical condition examination on milkfish preservation samples using 65 gr turmeric grated effectively preserved at the contact time of 23 hours while the contact time of 24 hours has been damaged. While the milkfish without treatment have suffered damage in the span of 8 hours.The conclusion obtained is that grated turmeric is better able to preserve milkfish in a long time compared to using turmeric solution. Suggestion We recommend using turmeric natural preservatives with grated turmeric to preserve milkfish because the durability of using turmeric grated is longer compared to the turmeric solution seen from physical conditions.